TINJAUAN SEMIOTIKA RIFFATERRE PADA CERPEN â€œBULAN KUNING SUDAH TENGGELAMâ€ KARYA AHMAD TOHARI - Heisma Arya Demokrawati; Widowati Widowati (CARAKA, 2015)
Â  Â  Â  Â  Â  Â  The objective of the study is to describe Riffaterre semiotikaâ€™s meaning of â€œBulan Kuning Sudah Tenggelamâ€ based on: 1) indirect expression, 2) reading of heuristic and hermeutik (retroactive), 3) finding matrix, model, and variant, 4) finding hipogram of â€˜Bulan Kuning Sudah Tengeelamâ€ short story. The research data were analyzed by qualitative techique. The source of the data was â€œBulan Kuning Sudah Tenggelamâ€ short story by Ahmad Tohari. The population of the data was sentences and paragraphs of an event that contained meaningful sign in â€œ Bulan Kuning Sudah Tenggelamâ€. The research instrument was researcher who were armed with the concept of meaningful sign system by semiotic theory. The data collecting method of this study was hermeneutika method andÂ  the data collecting techniques were read, write, and book. For the data analysis techinque, the researcher used descriptive qualitative and descriptive analysis method. The results of this research were: 1) the indirect expression consisted of (a) change of meaning, such as kiri-kanan (metomini) replaced by neighbour (b) deviation meaning, such as Oh that was a deviation meaning of admiration, apologetic, wonder, and understanding (c) the creation of meaning, such as //Apabila//, //Apabila//, //Apabila//, //Apabila// that was ended by same vocal //a// //a// //a// 2) reading of heuristic could be found by explicit and reading by hermeneutik could be found by implicit 3) the matrix was rebellion: the model was moon: the variants were the main problems in the story 4) the hipogram was Roman Bumi Manusia novel by Pramoedya Ananta Toer.